Ocular Manifestations of Diabetes Mellitus in Patients Attending Tertiary Care Hospital in Pondicherry, India - Raman, Nivedha S.; Hansdak, Amod; Sanjana, Elfride Farokh (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
Introduction: This study was undertaken to find out the ocular manifestations of diabetes mellitus among diabetics reporting to a tertiary health care facility in Pondicherry. Aims: The objectives of this study are (1) To study socio-demographic details in relation to ocular manifestations of DM (2) To correlate the ocular manifestations with duration of diabetes. Materials and Methods: Seventy diabetic patients reporting to Ophthalmology outpatient department were studied during the months of August and September 2017. A predesigned questionnaire was used to interview the diabetics, anterior segment examination was carried out using torchlight and slit lamp, and +90D lens was used for fundus examination. The findings were recorded and analyzed using Microsoft Excel and Epidata respectively. Results: Most of the study subjects belonged to the age group 41-70 years, literate, employed, and middle-income group. Diabetic retinopathy was more in participants having diabetes for a duration of 10 or more years which was similar to the findings in many studies where disease duration was found to be a significant risk factor for diabetic retinopathy, and independent of adequacy of glycemic control. Conclusion: Healthcare providers need to focus their efforts on preventive measures to delay the onset of complications of diabetes. The importance of screening for diabetes and diabetic retinopathy and regular follow-up cannot be overemphasized in order to reduce the burden of disease and its devastating consequences.